2018
DOI: 10.2320/matertrans.m2018131
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Calcium Addition for Fabricating Aluminum Foams with Different Pore Sizes

Abstract: This study mainly investigated the influence of Calcium (Ca) addition on the pore size of aluminum foams made by using CuTiH 2 composite powder as foaming agent. The Ca addition required for fabricating aluminum foams with different pore sizes was experimentally investigated. Two possible foam stabilization mechanisms were discussed and compared. For foams with pore size about 3 mm, the optimized Ca addition is 1 mass%. For foams with pore size about 2 mm, the optimized Ca addition is 3 mass%³5 mass%. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In foam metal preparation process, particles or other elements are usually added to improve the stability of foam structure. For example, Ca is added to the melt and stirred in the ambient atmosphere to form the oxide inside metal melts to achieve foam stability, which is also called thickening (Miyoshi et al, 2000;Song et al, 2000;Heim et al, 2017;Cheng et al, 2018). Moreover, Fe or Si has been added in the basic alloy AlSi9Mg0.6 in the first stage of solidification of eutectic alloys to foam Primary Fe and Si-rich crystals which can improve the foam stability (Heim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In foam metal preparation process, particles or other elements are usually added to improve the stability of foam structure. For example, Ca is added to the melt and stirred in the ambient atmosphere to form the oxide inside metal melts to achieve foam stability, which is also called thickening (Miyoshi et al, 2000;Song et al, 2000;Heim et al, 2017;Cheng et al, 2018). Moreover, Fe or Si has been added in the basic alloy AlSi9Mg0.6 in the first stage of solidification of eutectic alloys to foam Primary Fe and Si-rich crystals which can improve the foam stability (Heim et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Modern trends in the development of methods of plastic deformation of materials are aimed at intensifying production processes by reducing the number of technological transitions from the base workpiece to the final product and is associated with an increase in the degree of deformation of the material in one technological cycle. Among these directions can be identified: the formation of products from materials in the solid-liquid state [1][2][3][4][5][6][7] and the production of products from inhomogeneous, usually porous, materials [8][9][10][11][12][13][14][15]. The main feature of these processes is that the material of the deformable workpiece, in contrast to the traditional processes of processing materials by pressure, has certain values of the initial porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium is a well-known bubble-stabilizing agent, its addition leads to the formation of various intermetallic phases and oxides, which increases the viscosity of the liquid aluminum. [7,8] It is believed that oxide particles (e.g., CaO and CaAl 2 O 4 ) could contribute to the stability of Al foam by its accumulation on the liquid film of bubbles, which prevents the rupture of metallic films by the elasticity created among bubbles [9] and hinder the drainage of the liquid via the foam structure. [10,11] Kaptay et al [12] suggested various scenarios to predict the stabilization of Al foam with various oxides according to their different wettability (contact angle).…”
mentioning
confidence: 99%